TATA KELOLA TERHADAP KECURANGAN LAPORAN KEUANGAN DENGAN AUDIT DELAY SEBAGAI MODERASI - Tjia, Febiana Suryono; Dwi Hayu Estrini; Melisa Anggraini (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Financial statement fraud represents a critical issue that can damage stakeholder trust and reduce the overall quality of corporate financial information. This study aims to examine the influence of audit committees and managerial ownership on the potential for financial statement fraud, as well as to evaluate the moderating role of audit delay. A quantitative approach was employed using secondary data from 55 public companies across the ASEAN region (Indonesia, Malaysia, the Philippines, and Vietnam) during the period 2015 – 2023, resulting in 495 observations. The sample was selected using a purposive sampling method, while the analytical techniques applied were multiple linear regression and Moderated Regression Analysis (MRA). The findings reveal that audit committees have a significant negative effect on financial statement fraud, and managerial ownership also shows a significant negative influence. Furthermore, audit delay is proven to moderate the relationship between audit committees and financial statement fraud, as well as the relationship between managerial ownership and financial statement fraud. These results align with agency theory and the fraud triangle, emphasizing the importance of internal monitoring and timely audits in reducing opportunities for manipulation. Overall, all hypotheses in this study are supported. The study offers practical implications for companies, auditors, and regulators in enhancing the effectiveness of monitoring mechanisms to prevent financial statement fraud.